The Relationship of Characteristics Adults Post-Stroke On Increasing Muscle Strength Rehabilitation In Bukittinggi City 2023 - Kasrin, Rinawati; Mohd Said, Faridah; Sansuwito, Tukimin Bin; Jafri, Yendrizal (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Introduction: Stroke is the third leading cause of death in the world. Long-term disability and paralysis becomes a burden for living stroke survivors. Disability results from muscle and nerve weakness upper and lower extremities. This research aims to identify the relationship between individual characteristics and history of stroke with muscle strength in stroke rehabilitation patients at home, Bukittinggi 2023. Materials and Methods: This research was conducted from May to June 2023. This study uses a cross-sectional descriptive analysis approach with questionnaires and Manual Muscle Testing (MMT). The total sample in this study was 42 respondents, using univariate and bivariate data. Data processing results using SPSS version 2.0 with the Qhi-Square Test. Results: based on gender showed that men were dominant at 71.4%, marital status at 69%, and in terms of education the majority was a bachelor's degree at 38.1%. self-employed jobs get 35.7% and socio-economic average 45.2% > IDR 3,000,000., on muscle strength in post-stroke rehabilitation patients increased using the MMT method by 59.9%. Conclusion: there is no relationship between the characteristics of respondents (gender, marital status, education, employment and socio-economics) on increasing muscle strength in post-stroke rehabilitation patients at home with a p value greater than 0.05.